Narrations of the Fewest Women in the Sunnah of Abi Dawood - Ahmed, Ihsan Mergny (Journal of Islamic Sciences, 2021)
The study aimed at taking out and studying the attribution of the women companions' narrations in order to narrate the hadith in the Sunnahs of Abi Dawood, and to translate the narrators of these attribution, showing the sayings of scholars in order to find out about them. The study used the historical and analytical method to arrive at the results. The study concluded with a statement of the verdict on the chain of narrators of these hadiths, and their distinction in terms of validity and weakness. The study recommended paying attention to studying the hadiths that are not found in the two Sahihs, Bukhari and Sahih Muslim, and the narrations of the Companions in the Hadith narration, in order to know the status of their chain of narrators, because the Sunnah is the second source of Islamic legislation.
Keywords: Narration Al-Nisaa The fewest; Sunan Abi Dawood